2012
DOI: 10.1016/j.bbr.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Depressive-like behaviour of mice lacking cellular prion protein

Abstract: Cellular Prion Protein (PrP(C)) is known to mediate a protective role in several neurological conditions such as ischemia and epilepsy. However, so far, little information is available concerning the role of PrP(C) in psychiatric disorders such as depression. Here, we have used PrP(C) null mice to examine a putative role of PrP(C) in depressive-like states. Prion protein null mice exhibited depressive-like behaviour when compared to wild-type mice in both the Forced Swimming Test (FST) and Tail Suspension Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
6
32
3
Order By: Relevance
“…On the other hand, in a study of wild-type and PrP C -null mice inbred into the FVB genetic background, no difference between 8 -12-week-old mice of either genotype were found in a forced swimming test (64), which differs from both our results (Fig. 1A), as well as of others (36). Notably, however, the FST in the Massimino study (64) was run for 3 min only, which differs greatly from the usual procedures, where the first 2 of a standard 6-min test are sometimes even discarded due to the hyperactivity of mice when introduced in the water pool (65).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, in a study of wild-type and PrP C -null mice inbred into the FVB genetic background, no difference between 8 -12-week-old mice of either genotype were found in a forced swimming test (64), which differs from both our results (Fig. 1A), as well as of others (36). Notably, however, the FST in the Massimino study (64) was run for 3 min only, which differs greatly from the usual procedures, where the first 2 of a standard 6-min test are sometimes even discarded due to the hyperactivity of mice when introduced in the water pool (65).…”
Section: Discussioncontrasting
confidence: 94%
“…Almost 40% of patients of sporadic Creutzfeldt-Jakob disease showed symptoms of major depression, a disorder linked to monoaminergic neurotransmission (34,35). Notably, PrP C -null mice reportedly showed signs of depressive-like behavior, which were corrected by imipramine, a tricyclic antidepressant that acts primarily as a monoamine reuptake inhibitor (36).…”
Section: Changes Were Reported In Prpmentioning
confidence: 99%
“…This was subsequently linked to increased depressive-like behavior and increased nociception in PrP C -deficient mice. Both phenotypes were rescued by pharmacological inhibition of NMDA receptors [91, 92]. Additionally, copper-dependent interaction of PrP C with the GluN1 subunit was documented, which was involved in nitrosylation of NMDA subunits GluN2A and GluN1.…”
Section: Possible Functions For Prpc Are Suggested By Interaction Parmentioning
confidence: 99%
“…[38][39][40] Taken together, these results point to modified or unbalanced neurotransmission. Indeed, a pioneer study by Walz et al demonstrated that mice devoid of PrP C were more sensitive to kainate, pentylenetetrazol (PTZ) and pilocarpine injections.…”
Section: Can Prp C Partners Be Responsible For the Differences In Obsmentioning
confidence: 97%